'Fodbold, det er da ikke noget for piger' - om Boldklubben Femina og dens kamp for at få fodbold accepteret som en sport for kvinder - Brus, Anne (Forum for Idræt, 2002)
Artikel om kvindefodbold, kampen om ligestilling inden for denne sport og dannelsen af DKFU. »Football! Why, that’s not for girls« – On the ball sports club, Femina, and its struggle to get football accepted as a sport for women In 1971 the female Danish football club BK Femina became the unofficial world champions in women’s football. Their success of the field was not an accident and has to be seen against the background of more than 10 years of fighting to get women’s football accepted as a sport for women. Taking as its starting point BK Femina’s sporting success, this article reveals which factors played a part in enabling women’s football to establish itself in Denmark as a sporting activity for women during the period 1959 to 1972, at which point women’s football was permitted entry into the national football league, the Danish Ballgames Union (DBU). It is suggested in the article, then, that acceptance of football as a sport for women must be seen in relation to the perception of what is understood as accepted feminine and masculine sporting practice, and in what way this understanding of gender in football altered over time in the period under analysis. Central to this process of change is the collaboration of mutual interests built up by women’s football, the media and sponsors.